Implementation of Total Quality Management in Tahfidz Education at SMA Muhammadiyah 1 Ponorogo - Katni, Katni; Arifin, Syamsul; Erwahyudin, Devid Dwi (MUADDIB Jurnal Kependidikan dan Keislaman, 2023)
Education quality management is an important agenda so that it continues to exist and be in demand by students from time to time. Current facts show that the quality of Islamic education is less of a serious concern for education managers, so that there are fewer students, and even to death do not get students.Â  This educational institution is often "less attractive" for students and guardians due to many things, such as the attitudes and services of educators, heads, and employees, the learning process, and infrastructure that ignore the quality of educational services. This reality is sad because thus educational institutions have lost their great potential as a place of education for generations as the successors of national and religious civilization. This research focuses on the implementation of total quality management in tahfidz education in senior high schools, which is expected to become a wealth in itself amid the development of the implementation of quality education services in Indonesia. Especially at the level of Islam-based high schools, which are concerned with the integration of science in aspects of Islam (Islamic studies), as well as social science and natural science.Â  Can be an inspiration for the development of Islamic high schools in Indonesia. This study is to describe the implementation of total quality management in tahfidz education at SMA Muhammadiyah 1 Ponorogo. Tahfidz education as one of the advantages at SMA Muhammadiyah 1 Ponorogo will be seen from the Total Quality management cycle (Pland-Do-Check-Action/PDCA).